Workplace communication : process and product / Sharon J Gerson, Steven M Gerson - Gerson, Sharon J.
"Workplace Communication: Process and Product provides you with the tools you will need to communicate effectively in the workplace in both written and oral formats. The text includes: Thorough Coverage of Communication Topics: All major communication channels, such as memos, letters, short reports, long reports/proposals, instructions, technical descriptions, resumes, and emerging electronic communication options, Issues of audience diversity, multiculturalism, and ethics, Strategies for everyday oral communication, informal oral presentations, and formal oral presentations, including PowerPoint use, Standards for APA and MLA documentation. Special Chapter Features: Communication at Work scenarios, Writer's Insight boxes, The Writing Process at Work features, Before and After examples, Document and Process checklists, Developing Workplace Skills exercises. Book jacket."